Salīdzinošs pētījums par mīksto audu sarkomu incidenci un to apakštipiem starp Traumatoloģijas un ortopēdijas slimnīcu, Rīgā, Latvijā un Somiju (Somijas audzēju reģistra dati) - Kivelä, Elli Erika (Latvijas Universitāte, 2024)
Ievads: Mīksto audu sarkomas ir reta audzēju grupa, kas sastāda ap 1% no visiem ļaundabīgajiem audzējiem. Tie rodas no mezenhimālām šūnām, un šie audzēji, pēc histoloģiskās, molekulāri bioloģiskās un klīniskās gaitas, ir heterogēni tumori. Atbilstoši Pasaules Veselības Organizācijas (PVO) klasifikācijai, ir vairāk nekā 70 dažādi sarkomu histopatoloģiskie apakšstipi. Sarkomu diagnostikas zelta standarts ir histopatoloģiskā izmeklēšana. Savukārt, sarkomu ārstēšana ir atkarīga no audzēja stadijas, tomēr, ķirurģiskā ārstēšana tiek uzskatīta par pamata ārstēšanas metodi, kas lokalizētu sarkomu gadījumā ir efektīva. Papildus tiek izmantotas staru terapija un ķīmijterapija. Darba mērķis: Mūsu pētījuma mērķis bija novērtēt sarkomu sastopamību Traumatoloģijas un Ortopēdijas slimnīcā, Rīgā un salīdzināt šos datus ar sarkomu incidenci Somijā, izmantojot Somijas audzēja reģistra pieejamu informāciju. Materiāli un metodes: Pētījums bija retrospektīvs. Pētījumā tika iekļauti pacienti, kuriem Traumatoloģijas un Ortopēdijas slimnīcā, Rīgā laika posmā no 2017. līdz 2021. gadam tika noteikta sarkomas diagnoze. Dati tika kodēti un anonimizēti un analizēti ar aprakstošās un korelatīvām statistikas metodēm, un pēc tam tika salīdzināti ar sarkomu incidenci Somijā, ņemot vērā Somijas audzēja reģistra datus. Rezultāti: 26 pacientiem laika posmā no 2017. līdz 2021. gadam Traumatoloģijas un Ortopēdijas slimnīcā tika noteikta sarkomas diagnoze. Somijā šajā laikā tika noteiktas 1151 sarkomu diagnozes. Latvijā 9 pacientes (34.6% gadījumā) bija sievietes, bet 17 pacienti (65.4% gadījumā) bija vīrieši. Savukārt, Somijā, 526 pacientes (45.7%) bija sievietes un 625 pacienti (54.3%) bija vīrieši. Mīksto audu sarkomu incidence pieauga līdz ar vecumu. Secinājumi: Pētījumā iegūtie rezultāti pirmo reizi parādīja mīksto audu sarkomu izplatību Latvijā un Somijā. Lielākā sarkomu sastopamība gan Latvijā, gan Somijā tika novērota vīriešiem. Turklāt, sarkomu incidence pieauga līdz ar vecumu. Pētījums parādīja lielāku sarkomu sastopamību Somijā uz 100 000 iedzīvotājiem. Pētījumā tika parādīta asociācija starp pacientes dzimumu un sarkomas diferenciācijas pakāpi, kas norāda, ka dzimums ir svarīgs sarkomu prognozes rādītājs.

Background: Soft tissue sarcomas are rare cancers that account for approximately 1% of all malignant tumors. They arise from mesenchymal cells and represent a widely heterogeneous group of neoplasms that are subclassified based on their histological characteristics, molecular analysis, and clinical course. According to the World Health Organization classification, there are more than 70 histological subtypes of soft tissue sarcomas. A definitive sarcoma diagnosis is established by obtaining a biopsy, which then undergoes histopathological evaluation. Treatment options vary depending on the stage of the tumor, with surgery generally considered the most effective approach. In cases of localized soft tissue sarcomas, surgery can be curative, and additional treatment modalities include radiation and chemotherapy. Aim: The aim of the study was to compare the incidence of soft tissue sarcomas and their various types at the Hospital of Traumatology and Orthopaedics in Riga, Latvia, which is a central referral center for such cases and in Finland, by analyzing the Finnish Cancer Registry data, an official source for soft tissue cancer statistics. Materials and methods: The study was carried out Retrospectively and the information about the sarcoma cases from the archive of the Laboratory of Microbiology and Histopathology, Hospital of Traumatology and Orthopaedics was randomly selected from the years 2017-2021. The cases were coded, and the data was anonymized. The Latvian data was compared with the Finnish Cancer Registry soft tissue sarcoma incidence and histopathological subtypes during 2017-2021. Results: In total during the years 2017-2021 26 soft tissue sarcoma cases were diagnosed in the Hospital of Traumatology and Orthopaedics in Riga. In Finland, 1151 cases of soft tissue sarcoma were diagnosed at the same time. In Latvia, the patient group consisted of females 34,6% (n=9), and males 65,4% (n=17), and in Finland 45,7% (n=526) were females, and 54,3% (n=625) were males. The soft tissue sarcoma incidence increases with age. Conclusions: In conclusion, the analysis revealed several findings regarding the epidemiology of soft tissue sarcomas in Finland and Latvia. Firstly, a higher incidence of soft tissue sarcomas was observed among men in both countries, highlighting gender differences in this malignancy. Secondly, the soft tissue sarcoma incidence increases with age. Additionally, the study indicated higher incidence rates per 100,000 in Finland compared to Latvia, suggesting potential differences in risk factors or diagnostic practices between the two nations. Lastly, an association was identified between gender and sarcoma grade, indicating that gender plays a significant role in the incidence, prognosis, and mortality rates. These findings provide insights into the epidemiological patterns of soft tissue sarcomas, which may help in future research and healthcare interventions aimed at reducing the burden of this disease.
Comparative study of the incidence of soft tissue sarcoma and its subtypes in hospital of Traumatology and Orthopaedics, Riga, Latvia and in Finland (Finnish cancer registry data)
Keywords: Medicīna; Sarcomas; Soft tissue sarcoma; Incidence; Latvia; Finland